2018
DOI: 10.1016/j.drugalcdep.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to parental substance use disorders increase offspring risk for a substance use disorder? A longitudinal follow-up study into young adulthood

Abstract: Exposure to maternal SUD increases the risk for an alcohol use disorder in offspring ten years later in young adult years irrespective of ADHD status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…AUD because the presence of a parent with AUD in the household is linked with high levels of conflict, aggression and violence (30)(31)(32). Studies on the effects of living with a parent with AUD are, however, inconclusive as higher risks of harmful drinking patterns and AUD has been found among offspring who live together with, as opposed to apart from, a parent with AUD in some studies (19,21,24), while no evidence for an association has been found in other studies (33,34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AUD because the presence of a parent with AUD in the household is linked with high levels of conflict, aggression and violence (30)(31)(32). Studies on the effects of living with a parent with AUD are, however, inconclusive as higher risks of harmful drinking patterns and AUD has been found among offspring who live together with, as opposed to apart from, a parent with AUD in some studies (19,21,24), while no evidence for an association has been found in other studies (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that offspring of parents with alcohol use disorder (AUD) are at high risk of growing up in a non-intact family (19)(20)(21)(22)(23)(24). Previous research concerning family structures among offspring of parents with AUD has been based on single or few assessments at specific ages (19)(20)(21) or as single measures covering the entire upbringing (22)(23)(24). Family structures are, however, dynamic with many possible trajectories over time (7), and a detailed overview is therefore warranted to gain a more comprehensive understanding of whom offspring with parental AUD grow up with.…”
Section: Introductionmentioning
confidence: 99%
“…Even when drug use is discontinued/controlled, psychological and relational dynamics underlying the development of parenting may be affected, limiting reflective parental functioning and challenging the quality of the parent–child relationship (57). Exposure to parental substance use eventually increases the risk of SUDs (61, 62) and other mental health problems in offspring (63, 64), which might install an intergenerational cycle of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal substance use can impact child development adversely, since it not only increases the risk for disruptive attachment patterns (73), but also for SUDs in offspring. Adverse childhood experiences, including growing up in a context of maternal substance use (74), predicts an earlier age of onset for alcohol (62, 75) and other drug use (76, 77), and increased odds for attempting suicide (78). A positive relationship was found between maternal substance use and the occurrence of child maltreatment, indicating a clear link with insecure attachment in children and adults (65).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal, but not, paternal SUD increased the risk of alcohol use disorder in offspring. Although, paternal SUD is not shown to be protective against alcohol use disorder, it does not enhance risk (Yule et al, 2018). Looking forward, it would be beneficial if preclinical and human work parallel each other when investigating the role of paternal drug consumption.…”
Section: Discussionmentioning
confidence: 99%